2018
DOI: 10.1186/s13104-018-3556-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal helminths and associated factors among school children of Medebay Zana wereda; North Western Tigray, Ethiopia 2017

Abstract: ObjectiveTo assess the prevalence of intestinal helminth infections and associated factors among primary school children of Medebay Zana wereda, a northwestern zone of Tigray, northern Ethiopia from March to April 2017.ResultThe prevalence of intestinal helminths was 12.7%. The highest prevalence of intestinal helminth infections was observed in the age group of 11–14 years old and the most prevalent helminths species were Schistosoma mansoni. Mothers’ level of education [AOR = 0.27 [0.13–0.58]], place of defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
27
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
10
27
10
Order By: Relevance
“…The overall prevalence of A. lumbricoides in this study was lower than what was observed in school-age pupils of rural areas of Southern China (18.5%) [34]; southern rural Lao People's Democratic Republic (PDR) (27.4%) [35]; Jimma, Ethiopia (23.6%) [25]; Zana wereda, Ethiopia (11.5%) [4]; Ogun State, Nigeria (29.3%) [31]; and Jos, Nigeria (25.7%) [32]. The possible reason for the higher prevalence in those studies compared with this study could be that the environment of where those studies were carried out may be more favorable for completion of the life cycle of the parasite such as fertile soil, and humid and wet environment.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The overall prevalence of A. lumbricoides in this study was lower than what was observed in school-age pupils of rural areas of Southern China (18.5%) [34]; southern rural Lao People's Democratic Republic (PDR) (27.4%) [35]; Jimma, Ethiopia (23.6%) [25]; Zana wereda, Ethiopia (11.5%) [4]; Ogun State, Nigeria (29.3%) [31]; and Jos, Nigeria (25.7%) [32]. The possible reason for the higher prevalence in those studies compared with this study could be that the environment of where those studies were carried out may be more favorable for completion of the life cycle of the parasite such as fertile soil, and humid and wet environment.…”
Section: Discussioncontrasting
confidence: 76%
“…The overall prevalence of hookworms in this study was higher than those reported in studies conducted in Chencha town, Ethiopia (2.2%) [23] and Babile town, Ethiopia (6.7%), [36] and almost similar to that of Jimma town, Ethiopia (12.9%) [37] but lower than that observed in Zana wereda, Ethiopia (32.7%) [4]. Hookworms were the most prevalent and the most widespread STH parasite in Kogi East.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, a study conducted in Babile town, Eastern Ethiopia reported a 27.2% prevalence of intestinal helminths. [17]. A. lumbricoides and T. trichiura are the commonest and widely distributed parasites throughout Ethiopia [18].…”
Section: Introductionmentioning
confidence: 99%
“…In African countries, students have a higher rate of schistosomiasis infection [28], as well as in Zanzibar [29]. In addition to preventive chemotherapy, other social, environmental and health interventions for schistosomiasis control in Zanzibar are implemented slowly now, if the schistosomiasis health education is not popularized, it is difficult to achieve the elimination level of schistosomiasis control in local area.…”
Section: Discussionmentioning
confidence: 99%